AC power load controlling by using PWM based on phase locked loop - Kitipongwatana, A.; Koseeyaporn, P.; Koseeyaporn, J.; Wardkein, P. (My University, 2009)
This paper proposes power load controlling by using PWM signal to on-off an electronic switch. With this technique, load current can be easily adjusted. For PWM signal, it is derived by using PLL. With the property of PLL, PWM signal whose frequency is synchronized with that of load power is generated. Consequently, phase of signal which is fed to load can be controlled all range of 360 degrees or 180 degrees. In addition, the experiment results show that linear relation between phase of signal and DC voltage. ©2009 IEEE.
Keywords: Phase locked loop; PWM